Isobaric Vapour-Liquid Equilibria of p-Xylene-2-Nitrotoluene System at 730 ± 2 mm Hg - Rattan, V.K.; Kapoor, Seema (Asian Journal of Chemistry, 2010)
Isobaric vapour-liquid equilibrium data were obtained for the system p-xylene-2-nitrotoluene at 730 ± 2 mm Hg pressure using a vapour recirculating type (modified Othmers) equilibrium still. The activity coefficients were obtained by taking into consideration the vapour phase non-ideality based on the pure component and mixture properties. The experimental data for the system was tested for thermodynamic consistency and correlated by various equations.